KUALITAS PELAYANAN PEMOTONGAN HEWAN PADA RUMAH POTONG HEWAN KABUPATEN LAMPUNG BARAT - Endang Kuroini; Achmad Suharyo (e-JKPP, 2023)
The formulation of the problems in this study are: (1) How is the quality of slaughter services service quality in West Lampung Regency Slaughterhouse (RPH), (2) What are the aspects thataspects that hinder the implementation of the Quality of Slaughterhouse Services in West Lampung Regency West Lampung Regency. The research method used in this research is to use qualitative research with descriptive analysis method. The results showed that the Quality of Slaughterhouse Services in West Lampung Regency Slaughterhouse (RPH), through aspects, (1) Reliability, (2) Responsiveness, (3) Certainty, (4) Empathy, (5) Tangible, has been implemented by the apparatus, and carry out according to tupoksi. Aspects that hinder the quality of slaughterhouse services in West Lampung Regency, namely (1) Not yet fully created Publik awareness; (2) Lack of animal transport vehicle facilities; (3) Lack of socialization by the government, so that people who are busy with work do not know the benefits and procedures for using the West Lampung Regency Slaughterhouse (RPHKUALITAS PELAYANAN PEMOTONGAN HEWAN PADA RUMAH POTONG HEWAN KABUPATEN LAMPUNG BARAT